A Q-Theory of Banks - Juliane Begenau; Saki Bigio; Jeremy Majerovitz; Matias Vieyra (Center for Economic Studies and ifo Institute (CESifo), 2021)
We propose a dynamic bank theory with a delayed loss recognition mechanism and a regulatory capital constraint at its core. The estimated model matches four facts about banks' Tobin's Q that summarize bank leverage dynamics. (1) Book and market equity values diverge, especially during crises; (2) Tobin's Q predicts future bank profitability; (3) neither book nor market leverage constraints are binding for most banks; (4) bank leverage and Tobin's Q are mean reverting but highly persistent. We examine a counterfactual experiment where different accounting rules produce a novel policy tradeoff.
Keywords: G21; G32; G33; E44; 330; banks; leverage dynamics; market vs. book values; delayed accounting